Salivary protein candidates for biomarkers of oral disorders in people with a crack cocaine use disorder - Cassiano Lima CHAIBEN; Nayara Flores MACEDO; Thiago Beltrami Dias BATISTA; Carlos Antonio Schaffer PENTEADO; Talita M. O. VENTURA; Aline DIONIZIO; Paulo Henrique Couto SOUZA; Marília Afonso Rabelo BUZALAF; Luciana Reis AZEVEDO-ALANIS (University of São Paulo, 2023)
Abstract The use of cocaine and its main derivative, crack, can cause some systemic effects that may lead to the development of some oral disorders. Objective To assess the oral health of people with a crack cocaine use disorder and identify salivary protein candidates for biomarkers of oral disorders. Methodology A total of 40 volunteers hospitalized for rehabilitation for crack cocaine addiction were enrolled; nine were randomly selected for proteomic analysis. Intraoral examination, report of DMFT, gingival and plaque index, xerostomia, and non-stimulated saliva collection were performed. A list of proteins identified was generated from the UniProt database and manually revised. Results The mean age (n=40) was 32 (±8.88; 18-51) years; the mean DMFT index was 16±7.70; the mean plaque and gingival index were 2.07±0.65 and 2.12±0.64, respectively; and 20 (50%) volunteers reported xerostomia. We identified 305 salivary proteins (n=9), of which 23 were classified as candidate for biomarkers associated with 14 oral disorders. The highest number of candidates for biomarkers was associated with carcinoma of head and neck (n=7) and nasopharyngeal carcinoma (n=7), followed by periodontitis (n=6). Conclusions People with a crack cocaine use disorder had an increased risk of dental caries and gingival inflammation; less than half had oral mucosal alterations, and half experienced xerostomia. As possible biomarkers for 14 oral disorders, 23 salivary proteins were identified. Oral cancer and periodontal disease were the most often associated disorders with biomarkers.